Morphometric Variations of Discophrya elongata (Ciliophora, Suctorea) Attached to Two Different Species of Aquatic True Bugs (Hemiptera, Prosorrhyncha, Nepomorpha) - Marino-Perez, R.; Mayen-Estrada, R.; Macip-Rios, R.; Dovgal, I.V. (Вестник зоологии, 2011)
Morphometric variation in Discophrya elongata living as epibionts of two species of aquatic true bugs, Corisella edulis and Notonecta unifasciata, collected from the same pond in Mexico are discussed. Factors that may be responsible for observed variability, especially hydrodynamic loads and long-term modifications, also are identified and discussed. В статье обсуждается изменчивость размерных характеристик полиморфного вида сукторий Discophrya elongata при поселении на двух видах водных клопов Corisella edulis и Notonecta unifasciata из одного местообитания – пруда в Мексике. Указаны факторы, с которыми могут быть связаны наблюдаемые различия в размерах вида, в частности, гидродинамические нагрузки и длительные модификации.